EURAD State-of-the-Art Report: ACED assessment of the chemical evolution at the disposal cell scale—part I—processes at interfaces and evolution at disposal cell scale - Neeft, Erika; Deissmann, Guido; Jacques, Diederik (Frontiers in Nuclear Engineering, 2025)
Within the framework of the European Joint Programme on Radioactive Waste Management, the work package ACED–Assessment of chemical evolution of intermediate level (ILW) and high level (HLW) waste at disposal cell scale–used combined experimental and modelling methods in a multi-scale approach with process integration to improve the long-term modelling and assessment of the chemical evolution at the disposal cell scale. Part I provides the relevance of the assessment of the chemical evolution for safety, performance, and optimization. It further describes the main characteristics of disposal cells for ILW and vitrified HLW waste in European disposal programmes. From that, a number of interfaces between different types of material are identified that are highly relevant for many national disposal programs: glass-steel, steel-concrete, steel-clay, steel-crystalline, concrete-clay, and concrete-crystalline. Based on literature review, the main processes and consequences occurring at these interfaces are described. The key element is the narrative of the evolution at the disposal cell scale based on process understanding. In part II, tools to obtain process understanding–experiments, analogues, modelling–are discussed in detail.